Production process of environment-friendly gloves

By using aqueous nitrile emulsion and carbon nanotube composite materials in the glove production process, combined with specific stirring and molding steps, the problems of solvent contamination and high production costs in the existing process are solved, and environmentally friendly, efficient and high-strength glove production is achieved.

CN119708558APending Publication Date: 2025-03-28NANTONG QINGPAN SAFETY PROTECTION TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411635015.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The solvents used in the existing glove production process cause wastewater and waste gas pollution and cause toxic damage to workers, while increasing production costs.

Method used

A kind of environmentally friendly glove production process is adopted. By stirring nitrile latex with crosslinking agent, potassium hydroxide aqueous solution, foam stabilizer, sulfur dispersion, accelerator and zinc oxide dispersion, carbon nanotube composite material and thickener are added, and coagulation and surface treatment are avoided, and directly impregnated and dried to form.

Benefits of technology

The glove production process is achieved without coagulant and surface treatment, which reduces latex penetration and rubber cracks, improves production efficiency, and the addition of carbon nanotube composite materials improves the mechanical strength and mechanical properties of the gloves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005136936550000101
    Figure BDA0005136936550000101
  • Figure BDA0005136936550000111
    Figure BDA0005136936550000111
Patent Text Reader

Abstract

The invention relates to a production process of environment-friendly gloves, which comprises the following steps: adding a cross-linking agent into butyronitrile latex in a stirring state, continuously stirring, sealing and standing, adding a potassium hydroxide aqueous solution and a foam stabilizer, stirring, adding a sulfur dispersion, an accelerant dispersion and a zinc oxide dispersion into a system, stirring, and when the viscosity of the system is reduced, adding a foaming agent, and stirring to obtain the environment-friendly gloves. Adding water; adding a carbon nanotube composite material, and when the viscosity of the system is increased, increasing the stirring speed and adding water; adding a thickening agent, increasing the stirring speed, adding a cross-linking agent, keeping stirring, increasing the stirring speed when the viscosity of the system is increased, adding a latex stabilizer, and continuing stirring; stopping stirring, sealing, standing, filtering, adding water, and stirring for foaming; the glove lining is subjected to mold covering, then gum dipping is conducted, drying, vulcanization and ripening are conducted after gum dipping, and the environment-friendly glove is obtained. In the preparation process, coagulant dipping and surface treatment are not carried out, so that the preparation process is green, environment-friendly and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of gloves, and in particular to a production process of environmentally friendly gloves. Background Art

[0002] Conventional dipped labor protection gloves generally have a protective rubber surface on the outer surface of the inner lining. The protective rubber surface is generally made of nitrile rubber, natural latex, styrene-butadiene rubber, chloroprene rubber, polyurethane resin and other materials. Among them, nitrile rubber is widely used in the production of protective rubber surfaces of labor protection gloves due to its excellent wear resistance, oil resistance and chemical resistance. Among them, nitrile rubber foam dipped gloves are mass-produced and sold due to their breathability and comfortable wearing characteristics.

[0003] In the prior art, when preparing rubber foam gloves, surface treatment is required. The surface treatment is generally one or more of xylene, benzoic acid, calcium nitrate, glacial acetic acid, and sodium sulfate to solidify or sand the surface. However, these solvents and the like can cause wastewater and waste gas pollution and cause toxic harm to workers, while also increasing production costs. Summary of the invention

[0004] In order to improve the preparation efficiency of gloves, the present application provides a production process of environmentally friendly gloves.

[0005] The production process of an environmentally friendly glove provided in this application adopts the following technical solution: A production process of environmentally friendly gloves, comprising the following steps: S1. Add a crosslinking agent to the nitrile latex under stirring and continue stirring, then seal and let stand, add a 10% by mass potassium hydroxide aqueous solution and a foam stabilizer and stir, add a sulfur dispersion, a accelerator dispersion and a zinc oxide dispersion to the system and stir, when the viscosity of the latex system increases significantly, increase the stirring speed to keep the surface of the system in a fluid state, continue stirring, and when the viscosity of the system decreases, add water to reduce the viscosity of the system; S2, adding the carbon nanotube composite material to the system and maintaining the stirring state, when the viscosity of the system increases, increasing the stirring speed, and then adding water to reduce the viscosity of the system; S3, adding thickener and increasing stirring speed, then adding crosslinking agent and keeping stirring, when the viscosity of the system increases, increasing stirring speed, adding latex stabilizer and continuing stirring to make the latex system react completely; S4, stop stirring, seal and let stand, filter and stir after standing, then add water to reduce the viscosity of the system, and then stir to foam; S5, put the glove liner into the mold, then dip in glue, dry and vulcanize after dipping in glue, and obtain environmentally friendly gloves.

[0006] By adopting the above technical scheme, when preparing gloves, the present application immerses the glove lining in the aqueous nitrile emulsion and then dries and forms the glove lining with the aqueous nitrile emulsion on the surface. In the preparation process, no coagulant is used to immerse the gloves, and no further surface treatment is performed on the latex gloves. In the preparation process of the latex gloves without the coagulation, immersion and surface treatment steps, the latex will not penetrate into the glove lining, and cracks will not appear on the rubber surface. The steps of preparing the latex gloves are reduced, and the gloves are green and environmentally friendly, and the production efficiency is improved. At the same time, the addition of carbon nanotube composite materials in the preparation process can effectively improve the mechanical strength of the latex gloves, thereby improving the mechanical properties of the latex gloves.

[0007] Preferably, the step S5 specifically includes the following steps: Put the glove liner on the hand mold, preheat the glove liner, then dip it in glue, take the glue out of the dipped gloves, remove the excess glue, heat and dry, soak in water to clean, and finally dry, vulcanize and mature to obtain environmentally friendly gloves.

[0008] Preferably, the carbon nanotube composite material comprises modified carboxyl carbon nanotubes, modified graphene and ferrosoferric oxide.

[0009] By adopting the above technical scheme, modified graphene oxide is an important derivative of graphene. Graphene is a two-dimensional material formed by a single layer of carbon atoms arranged in a hexagonal lattice and has good mechanical properties. Graphene oxide is obtained after oxygen-containing groups are introduced on the surface of graphene, so that the performance of graphene is further improved. Ferroferric oxide promotes the stability of latex. Modified carboxyl carbon nanotubes are a one-dimensional carbon material with good mechanical and thermal properties. The three are combined to form a stable three-dimensional system, which can synergistically promote the stability of the latex system, thereby improving the product quality and mechanical properties of the prepared gloves.

[0010] Preferably, the modified graphene oxide comprises 2-methylimidazole and graphene oxide.

[0011] By adopting the above technical solution, 2-methylimidazole has good antibacterial properties and can form a stable structure after being compounded with graphene oxide. Graphene oxide can enhance the physical damage to bacteria, thereby synergistically improving the overall antibacterial properties of the system.

[0012] Preferably, the modified graphene oxide is prepared by the following method: 2-methylimidazole and methanol are mixed to obtain a 2-methylimidazole solution, zinc nitrate hexahydrate and methanol are mixed to obtain a zinc nitrate solution, graphene oxide, water and methanol are mixed, ultrasonicated, and then mixed with the zinc nitrate hexahydrate solution, stirred, 2-methylimidazole solution is added, ultrasonically stirred to obtain a seed solution, and the seed solution is dried to obtain seeds; after mixing the prepared seeds with methanol, 2-methylimidazole and cobalt nitrate hexahydrate are added, ultrasonically stirred, centrifuged for washing, and dried to obtain modified graphene oxide.

[0013] By adopting the above technical scheme, Zn atoms and Co atoms can form a tetrahedral configuration with 2-methylimidazole, which has a high specific surface area, high crystallinity, and good chemical and thermal properties. At the same time, graphene oxide can further support the strength of the system. The strong interaction between Zn ions and the hydroxyl and carboxyl groups in the oxygen-containing groups of graphene oxide forms a sandwich structure. Graphene oxide damages the cell wall and cell membrane of bacteria by causing physical wear and structural damage, resulting in structural damage, and the release of metal ions and organic ligands, thereby playing a synergistic antibacterial role. The prepared modified graphene oxide has good stability and antibacterial properties.

[0014] Preferably, the mass ratio of the graphene oxide to 2-methylimidazole is 1:(2.2-2.4).

[0015] By adopting the above technical solution, the mass ratio between graphene oxide and 2-methylimidazole is preferably within the above range, which can further improve the comprehensive performance of the prepared modified graphene oxide.

[0016] Preferably, the carbon nanotube composite material is prepared by the following method: The modified graphene oxide is mixed with water and then ultrasonically treated to obtain a modified graphene oxide dispersion; modified carboxyl carbon nanotubes, ferric chloride and ferrous sulfate heptahydrate are added to the modified graphene oxide dispersion, and the mixture is stirred in a water bath for reaction; ammonia water is added while stirring; after the reaction is completed, a reducing agent is added for reduction to obtain a composite dispersion; the composite dispersion is dried to obtain a precipitate; the precipitate is naturally cooled and then washed to neutrality; the precipitate is centrifuged and then freeze-dried to obtain a carbon nanotube composite material.

[0017] By adopting the above technical scheme, the modified carboxyl carbon nanotubes and ferroferric oxide nanoparticles are loaded on the surface of the modified graphene oxide through the action of the reducing agent, and the prepared ternary composite material has good stability and mechanical strength, which can further improve and enhance the mechanical properties of the latex material, thereby improving the mechanical strength of the prepared latex gloves.

[0018] Preferably, the reducing agent comprises ammonium sulfide.

[0019] Preferably, the mass ratio of the modified graphene oxide, the modified carboxyl carbon nanotubes, ferric chloride and ferrous sulfate heptahydrate is (3.8-4.2):1:12:5.

[0020] By adopting the above technical solution, the mass ratio of modified graphene oxide, modified carboxyl carbon nanotubes, ferric chloride and ferrous sulfate heptahydrate is preferably within the above range, which can further improve the overall comprehensive performance of the prepared carbon nanotube composite material.

[0021] Preferably, the modified carboxyl carbon nanotubes are prepared by the following method: The polyethyleneimine is mixed with water to obtain a polyethyleneimine aqueous solution, the carboxylated multi-walled carbon nanotubes are added to the polyethyleneimine aqueous solution, condensed and refluxed in an oil bath, vacuum filtered and washed, and freeze-dried to obtain modified carboxyl carbon nanotubes.

[0022] By adopting the above technical scheme, polyethyleneimine is rich in primary and secondary amino groups, and polyethyleneimine is grafted to the surface of carboxylated carbon nanotubes through amidation reaction, so that the composite performance of carbon nanotubes is further improved, and the compatibility of carboxylated carbon nanotubes in the system is further improved, so that the stability of the system is improved.

[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. When preparing gloves, the glove lining is immersed in an aqueous nitrile emulsion, and then the glove lining with the aqueous nitrile emulsion on the surface is dried and formed. Not only is no coagulant used in the preparation process, but also no surface treatment is performed on the latex gloves. The latex gloves prepared by the process will not penetrate into the glove lining, and the occurrence of cracks on the rubber surface is reduced. The preparation steps reduce the steps of adding a coagulant and surface treatment, which is more environmentally friendly, and the production efficiency of the latex gloves is further improved. At the same time, the addition of a carbon nanotube composite material during the preparation can effectively improve the tensile strength of the prepared latex gloves; 2.2-Methylimidazole has good antibacterial properties. After being compounded with graphene oxide, it can form a stable structure. When zinc nitrate hexahydrate and cobalt nitrate hexahydrate are added, Zn atoms and Co atoms can form a tetrahedral configuration with 2-methylimidazole. At the same time, Zn ions can strongly interact with the hydroxyl and carboxyl groups of oxygen-containing groups in graphene oxide to form a sandwich structure, so that the prepared modified graphene oxide has good stability. At the same time, the release of metal ions and organic ligands, together with the physical wear and structural damage of graphene oxide, can play a good antibacterial role. 3. Modifying the surface of carbon nanotubes with polyethyleneimine can effectively improve the compatibility and mechanical strength of carbon nanotubes. After being compounded with ferroferric oxide and modified graphene oxide, a stable ternary structure is formed. After being combined with the latex system, the overall mechanical strength and tensile properties of the latex system can be further improved, thereby making the prepared gloves more stable. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained commercially; the sulfur dispersion is obtained by ball-milling sulfur and water in a ball mill; the promoter dispersion is obtained by ball-milling the promoter and water in a ball mill, and the promoter is a mixture of equal amounts of sodium dodecylbenzenesulfonate (CAS No.: 25155-30-0) and propylene glycol (CAS No.: 57-55-6); the thickener is hydroxyethyl cellulose (CAS No.: 9004-62-0); the cross-linking agent is dimethyl bisthiocarbonyl disulfide (CAS No.: 137-26-8); and the latex stabilizer is 2,6-di-tert-butyl-4-methylphenol (CAS No.: 128-37-0).

[0025] Example 1 Preparation of modified carboxyl carbon nanotubes: Polyethyleneimine (CAS No.: 9002-98-6) was mixed with deionized water to prepare a polyethyleneimine aqueous solution with a concentration of 50 mg / L, and carboxylated carbon nanotubes were added to the polyethyleneimine aqueous solution to make the concentration of the carboxylated carbon nanotubes 1 mg / L. The system was placed in an oil bath, condensed and refluxed at 120° C. for 12 h, then vacuum filtered, washed with deionized water 5 times to remove excess polyethyleneimine, and freeze-dried in a vacuum freeze dryer at -20° C. for 12 h to obtain modified carboxyl carbon nanotubes.

[0026] Preparation of modified graphene oxide: 26.32 g of 2-methylimidazole (CAS No.: 693-98-1) was mixed with 150 mL of methanol to obtain a 2-methylimidazole solution. 11.94 g of zinc nitrate hexahydrate was mixed with 150 mL of methanol to obtain a zinc nitrate solution. 15.63 g of graphene oxide, 50 g of deionized water and 200 g of methanol were mixed and ultrasonicated for 30 min. Then, the mixture was mixed with the zinc nitrate hexahydrate solution and stirred for 30 min. Then, the 2-methylimidazole solution was added and ultrasonicated for 30 min. Then, the mixture was heated at 800 °C. r / min for 3 hours to obtain a seed solution, and the seed solution was dried at 80°C for 16 hours to obtain seeds; the prepared seeds were mixed with 200 mL of methanol, 8.05 g of 2-methylimidazole and 3.58 g of cobalt nitrate hexahydrate were added, and after ultrasonication for 30 minutes, the mixture was stirred at 800 r / min for 3 hours, and then centrifuged at 8000 r / min for 10 minutes, washed three times with methanol, and dried at 60°C for 12 hours to obtain modified graphene oxide.

[0027] Preparation of carbon nanotube composites: 34.86 g of modified graphene oxide was mixed with 400 mL of deionized water and ultrasonicated for 20 min to obtain a modified graphene oxide dispersion. Subsequently, 9.17 g of modified carboxyl carbon nanotubes, 110.12 g of ferric chloride, and 45.85 g of ferrous sulfate heptahydrate were added to the modified graphene oxide dispersion. The mixture was stirred for 2 h at a speed of 600 r / min in a water bath under nitrogen protection. 12 g of ammonia water was added while stirring. After the reaction, 30 mL of a reducing agent was added for reduction to obtain a composite dispersion. The composite dispersion was then dried in an oven at 60° C. for 3 h to obtain a precipitate. The precipitate was then allowed to cool naturally, and the cooled precipitate was washed to neutrality with deionized water. After centrifugation, it was freeze-dried at -20° C. for 48 h to obtain a carbon nanotube composite material.

[0028] Wherein, the reducing agent is ammonium sulfide (CAS No.: 12135-77-2).

[0029] Preparation of environmentally friendly gloves: S1. Add 8g of cross-linking agent to 800g of nitrile latex under stirring at a speed of 400r / min and continue stirring for 20min, then seal and let stand for 48h, add 4g of 10% potassium hydroxide aqueous solution and 4g of foam stabilizer and stir for 30min after standing, add 8g of sulfur dispersion, 4g of accelerator dispersion and 24g of zinc oxide dispersion to the system, stir at a speed of 400r / min, when the viscosity of the latex system increases significantly, increase the stirring speed to 600r / min, so that the surface of the system remains in a flowing state, continue stirring, when the viscosity of the system decreases, add 40g of water at the stirring speed, so that the viscosity of the system decreases to 500mpa.s, and adjust the stirring speed back to 400r / min; S2, adding 80g of the carbon nanotube composite material to the system and keeping stirring. When the viscosity of the system increases, the stirring speed is increased to 600r / min, and then 40g of water is added to reduce the viscosity of the system to 500mPa.s, and the stirring speed is adjusted back to 400r / min; S3, add 40g of thickener, and increase the stirring speed to 600r / min, then add 4g of cross-linking agent, keep stirring, when the viscosity of the system increases, increase the stirring speed to 800r / min, when the viscosity of the system reaches 8000mPa.s, add 16g of latex stabilizer, and continue stirring for 2h to allow the latex system to react completely; S4, stop stirring, seal and let stand for 15 hours, filter after standing, and stir for 10 minutes, then add water to make the viscosity of the system reach 1500mpa.s, then stir and foam at a speed of 1200r / min to make the bubble volume 5%; S5. The glove lining is molded and then dipped in glue. After dipping in glue, the glove lining is dried, vulcanized and matured at 55° C. to obtain environmentally friendly gloves.

[0030] Example 2 Preparation of modified carboxyl carbon nanotubes: Polyethyleneimine was mixed with deionized water to prepare a polyethyleneimine aqueous solution with a concentration of 50 mg / L, and carboxylated carbon nanotubes were added to the polyethyleneimine aqueous solution to make the concentration of the carboxylated carbon nanotubes 1 mg / L. The system was placed in an oil bath, condensed and refluxed at 120° C. for 12 h, then vacuum filtered, washed with deionized water 5 times to remove excess polyethyleneimine, and freeze-dried in a vacuum freeze dryer at -20° C. for 12 h to obtain modified carboxyl carbon nanotubes.

[0031] Preparation of modified graphene oxide: 27.03 g of 2-methylimidazole was mixed with 150 mL of methanol to obtain a 2-methylimidazole solution, 12.26 g of zinc nitrate hexahydrate was mixed with 150 mL of methanol to obtain a zinc nitrate solution, 14.71 g of graphene oxide, 50 g of deionized water and 200 g of methanol were mixed, ultrasonicated for 30 min, then mixed with the zinc nitrate hexahydrate solution, stirred for 30 min, and then added with the 2-methylimidazole solution, ultrasonicated for 30 min, and then heated at a speed of 800 r / min. The mixture was stirred for 3 hours to obtain a seed solution, and the seed solution was dried at 80°C for 16 hours to obtain seeds. The prepared seeds were mixed with 200 mL of methanol, and 8.26 g of 2-methylimidazole and 3.68 g of cobalt nitrate hexahydrate were added. After ultrasonication for 30 minutes, the mixture was stirred at 800 r / min for 3 hours, and then centrifuged at 8000 r / min for 10 minutes. The mixture was washed three times with methanol, and dried at 60°C for 12 hours to obtain modified graphene oxide.

[0032] Preparation of carbon nanotube composites: 37.84 g of modified graphene oxide was mixed with 400 mL of deionized water and ultrasonicated for 20 min to obtain a modified graphene oxide dispersion. Subsequently, 9.01 g of modified carboxyl carbon nanotubes, 108.1 g of ferric chloride, and 45.05 g of ferrous sulfate heptahydrate were added to the modified graphene oxide dispersion. The mixture was stirred in a water bath under nitrogen protection at a speed of 600 r / min for 2 h. 12 g of ammonia water was added while stirring. After the reaction, 35 mL of a reducing agent was added for reduction to obtain a composite dispersion. The composite dispersion was then dried in an oven at 60° C. for 3 h to obtain a precipitate. The precipitate was then allowed to cool naturally, and the cooled precipitate was washed to neutrality with deionized water. After centrifugation, it was freeze-dried at -20° C. for 48 h to obtain a carbon nanotube composite material.

[0033] Wherein, the reducing agent is ammonium sulfide.

[0034] Preparation of environmentally friendly gloves: S1, add 40g of cross-linking agent to 800g of nitrile latex under stirring at a speed of 400r / min and continue stirring for 20min, then seal and let stand for 48h, add 16g of 10% potassium hydroxide aqueous solution and 16g of foam stabilizer and stir for 30min after standing, add 16g of sulfur dispersion, 12g of accelerator dispersion and 40g of zinc oxide dispersion to the system, stir at a speed of 400r / min, when the viscosity of the latex system increases significantly, increase the stirring speed to 600r / min, so that the surface of the system remains in a flowing state, continue stirring, when the viscosity of the system decreases, add 80g of water at the stirring speed, so that the viscosity of the system decreases to 800mpa.s, and adjust the stirring speed back to 400r / min; S2, adding 160g of the carbon nanotube composite material to the system and keeping stirring. When the viscosity of the system increases, the stirring speed is increased to 600r / min, and then 80g of water is added to reduce the viscosity of the system to 800mPa.s, and the stirring speed is adjusted back to 400r / min; S3, add 80g of thickener, and increase the stirring speed to 600r / min, then add 16g of cross-linking agent, keep stirring, when the viscosity of the system increases, increase the stirring speed to 800r / min, when the viscosity of the system reaches 9000mpa.s, add 32g of latex stabilizer, and continue stirring for 2h to allow the latex system to react completely; S4, stop stirring, seal and let stand for 15 hours, filter after standing, and stir for 10 minutes, then add water to make the viscosity of the system reach 1500mpa.s, then stir and foam at a speed of 1200r / min to make the bubble volume 30%; S5. Put the glove liner on the hand mold, preheat the glove liner at a temperature of 35°C, and then dip the glove in glue. Take the dipped gloves out of the glue liquid, remove the excess glue liquid, heat and dry, and then soak them in deionized water for cleaning. Finally, dry and vulcanize them at 55°C to obtain environmentally friendly gloves.

[0035] Example 3 Preparation of modified carboxyl carbon nanotubes: Polyethyleneimine was mixed with deionized water to prepare a polyethyleneimine aqueous solution with a concentration of 50 mg / L, and carboxylated carbon nanotubes were added to the polyethyleneimine aqueous solution to make the concentration of the carboxylated carbon nanotubes 1 mg / L. The system was placed in an oil bath, condensed and refluxed at 120° C. for 12 h, then vacuum filtered, washed with deionized water 5 times to remove excess polyethyleneimine, and freeze-dried in a vacuum freeze dryer at -20° C. for 12 h to obtain modified carboxyl carbon nanotubes.

[0036] Preparation of modified graphene oxide: 26.69 g of 2-methylimidazole was mixed with 150 mL of methanol to obtain a 2-methylimidazole solution, 12.11 g of zinc nitrate hexahydrate was mixed with 150 mL of methanol to obtain a zinc nitrate solution, 15.15 g of graphene oxide, 50 g of deionized water and 200 g of methanol were mixed, ultrasonicated for 30 min, then mixed with the zinc nitrate hexahydrate solution, stirred for 30 min, and then added with the 2-methylimidazole solution, ultrasonicated for 30 min, and then heated at a speed of 800 r / min. The mixture was stirred for 3 hours to obtain a seed solution, and the seed solution was dried at 80°C for 16 hours to obtain seeds. The prepared seeds were mixed with 200 mL of methanol, and 8.16 g of 2-methylimidazole and 3.63 g of cobalt nitrate hexahydrate were added. After ultrasonication for 30 minutes, the mixture was stirred at 800 r / min for 3 hours, and then centrifuged at 8000 r / min for 10 minutes. The mixture was washed three times with methanol and dried at 60°C for 12 hours to obtain modified graphene oxide.

[0037] Preparation of carbon nanotube composites: 36.36 g of modified graphene oxide was mixed with 400 mL of deionized water and ultrasonicated for 20 min to obtain a modified graphene oxide dispersion. Subsequently, 9.09 g of modified carboxyl carbon nanotubes, 109.1 g of ferric chloride, and 45.45 g of ferrous sulfate heptahydrate were added to the modified graphene oxide dispersion. The mixture was stirred in a water bath under nitrogen protection at a speed of 600 r / min for 2 h. 12 g of ammonia water was added while stirring. After the reaction, 32 mL of a reducing agent was added for reduction to obtain a composite dispersion. The composite dispersion was then dried in an oven at 60° C. for 3 h to obtain a precipitate. The precipitate was then allowed to cool naturally, and the cooled precipitate was washed to neutrality with deionized water. After centrifugation, it was freeze-dried at -20° C. for 48 h to obtain a carbon nanotube composite material.

[0038] Wherein, the reducing agent is ammonium sulfide.

[0039] Preparation of environmentally friendly gloves: S1, add 24g of cross-linking agent to 800g of nitrile latex under stirring at a speed of 400r / min and continue stirring for 20min, then seal and let stand for 48h, add 10g of 10% potassium hydroxide aqueous solution and 10g of foam stabilizer and stir for 30min after standing, add 12g of sulfur dispersion, 8g of accelerator dispersion and 32g of zinc oxide dispersion to the system, stir at a speed of 400r / min, when the viscosity of the latex system increases significantly, increase the stirring speed to 600r / min, so that the surface of the system remains in a flowing state, continue stirring, when the viscosity of the system decreases, add 60g of water at a stirring speed, so that the viscosity of the system decreases to 650mpa.s, and adjust the stirring speed back to 400r / min; S2, adding 120g of the carbon nanotube composite material to the system and keeping stirring. When the viscosity of the system increases, the stirring speed is increased to 600r / min, and then 80g of water is added to reduce the viscosity of the system to 650mPa.s, and the stirring speed is adjusted back to 400r / min; S3, add 60g of thickener, and increase the stirring speed to 600r / min, then add 10g of cross-linking agent, keep stirring, when the viscosity of the system increases, increase the stirring speed to 800r / min, when the viscosity of the system reaches 8500mpa.s, add 24g of latex stabilizer, and continue stirring for 2h to allow the latex system to react completely; S4, stop stirring, seal and let stand for 15 hours, filter after standing, and stir for 10 minutes, then add water to make the viscosity of the system reach 1500mpa.s, then stir and foam at a speed of 1200r / min to make the bubble volume 20%; S5. The glove lining is molded and then dipped in glue. After dipping in glue, the glove lining is dried, vulcanized and matured at 55° C. to obtain environmentally friendly gloves.

[0040] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that when preparing modified graphene oxide, the amount of graphene oxide used is 17.24 g, the amount of 2-methylimidazole used in the 2-methylimidazole solution is 25.09 g, and the amount of 2-methylimidazole used for the second time is 7.67 g.

[0041] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that when preparing modified graphene oxide, the amount of graphene oxide used is 13.51 g, the amount of 2-methylimidazole used in the 2-methylimidazole solution is 27.95 g, and the amount of 2-methylimidazole used for the second time is 8.54 g.

[0042] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that zinc nitrate hexahydrate is not added when preparing the modified graphene oxide.

[0043] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that cobalt nitrate hexahydrate is not added when preparing modified graphene oxide.

[0044] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that when preparing the carbon nanotube composite, 30.19 g of modified graphene oxide, 9.43 g of modified carboxyl carbon nanotubes, 113.23 g of ferric chloride, and 47.15 g of ferrous sulfate heptahydrate are used.

[0045] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that when preparing the carbon nanotube composite, 42.11 g of modified graphene oxide, 8.78 g of modified carboxyl carbon nanotubes, 105.21 g of ferric chloride, and 43.9 g of ferrous sulfate heptahydrate are used.

[0046] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, when preparing the carbon nanotube composite, the modified carboxyl carbon nanotubes are replaced with ordinary carbon nanotubes.

[0047] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that when preparing the carbon nanotube composite, ferric chloride and ferrous sulfate heptahydrate are not added in Example 11, but are replaced by modified graphene oxide and modified carboxyl carbon nanotubes in a limited ratio.

[0048] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that when preparing the carbon nanotube composite, Example 12 replaces the modified graphene oxide with ordinary graphene oxide.

[0049] Embodiment 13 Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that when preparing the carbon nanotube composite, Example 13 only physically mixes the modified graphene oxide, the modified carboxyl carbon nanotubes and ferrosoferric oxide.

[0050] Embodiment 14 Example 14 is based on Example 3. The difference between Example 14 and Example 3 is that 60 g of carbon nanotube composite is added in Example 14.

[0051] Embodiment 15 Example 15 is based on Example 3. The difference between Example 15 and Example 3 is that 200 g of carbon nanotube composite is added in Example 15.

[0052] Comparative Example 1 Comparative Example 1 is based on Example 3. The difference between Comparative Example 1 and Example 3 is that in Comparative Example 2, the carbon nanotube composite is replaced with an equal amount of modified carbon nanotubes.

[0053] Comparative Example 2 Comparative Example 2 is based on Example 3. The difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the carbon nanotube composite is replaced by an equal amount of modified graphene oxide.

[0054] Comparative Example 3 Comparative Example 3 is based on Example 3. The difference between Comparative Example 3 and Example 3 is that no carbon nanotube composite is added in Comparative Example 1.

[0055] Performance testing The following performance tests were performed on the samples of Examples 1-15 and Comparative Examples 1-3: (1) Tensile strength performance test Based on GB / T528-2009 as the testing standard, the tensile strength performance test of the samples was carried out. Each sample was tested 3 times, the average value was taken, and the test structure was filled in Table 1.

[0056] (2) Antibacterial performance test Based on GB / T31402-2015 as the testing standard, the antibacterial performance of the samples was tested. Each sample was tested 3 times, the average value was taken, and the test results were filled in Table 1.

[0057] Table 1 Performance test results of Examples 1-15 and Comparative Examples 1-3 Data analysis Combined with Table 1, it can be seen that the tensile strength of Examples 1-3 is 26 MPa or above, indicating that the environmentally friendly gloves prepared in the present application have good tensile strength, the antibacterial rate of Escherichia coli in Examples 1-3 is 99.6% or above, and the antibacterial rate of Staphylococcus aureus is 99.8% or above, indicating that the environmentally friendly gloves prepared in the present application have good antibacterial properties.

[0058] In Examples 4-5, when preparing modified graphene oxide, the mass ratio of 2-methylimidazole to graphene oxide is not within the range specified in the present application. When the content of 2-methylimidazole is too much, the content of graphene oxide decreases, making it difficult to stably connect 2-methylimidazole, zinc nitrate and cobalt nitrate with graphene oxide, thereby reducing the overall performance of the system and affecting the overall performance of the system; when the content of 2-methylimidazole decreases, the overall antibacterial performance of the system is affected. At the same time, excessive graphene oxide agglomerates in the system, affecting the overall stability of the system. Therefore, the performance of Examples 4 and 5 are both reduced.

[0059] Zinc nitrate hexahydrate was not added in Example 6, and cobalt nitrate hexahydrate was not added in Example 7. It is difficult to form an organic bridge between graphene oxide and only one metal ion, and the support degree of the prepared modified graphene oxide is difficult to be further improved. At the same time, it is difficult to achieve synergistic antibacterial performance by using only one metal ion. Therefore, the performance of Examples 6 and 7 are both reduced.

[0060] In Examples 8 and 9, when preparing the carbon nanotube composite, the mass ratios of the modified graphene oxide, the modified carboxyl carbon nanotubes, ferric chloride and ferrous sulfate heptahydrate are not within the range defined in the present application. When the content of the modified graphene oxide is too much or too little, the stability of the binding performance of the ternary system is affected, resulting in a decrease in the performance of the prepared gloves. When the content of the modified graphene oxide decreases, the antibacterial performance of the system also decreases, so the performance of Examples 8 and 9 are both decreased.

[0061] In Example 10, the modified carboxyl carbon nanotubes are replaced with ordinary carboxyl carbon nanotubes. The compatibility of the carbon nanotubes that have not been modified with polyethyleneimine is reduced, and it is difficult to improve the dispersibility of the carbon nanotubes in the system, which reduces the stability of the carbon nanotube composite material in the system. Therefore, the performance of Example 10 is reduced.

[0062] In Example 11, no ferrosoferric oxide is added to the modified graphene oxide, and the bonding performance between the modified graphene oxide and the modified carboxyl carbon nanotubes is difficult to be further improved. At the same time, it is difficult to further improve the tensile performance of the latex system, so the performance of Example 11 is reduced.

[0063] In Example 12, only ordinary graphene oxide is used. The unmodified graphene oxide does not cooperate with metal ions to achieve antibacterial properties. The antibacterial properties of physical wear alone are reduced. At the same time, it is difficult to obtain a stable sandwich structure, so the mechanical strength is reduced. Therefore, the performance of Example 12 is reduced.

[0064] In Example 13, only modified graphene oxide, modified carboxyl carbon nanotubes and ferrosoferric oxide are physically mixed. It is difficult for the system with only ordinary mixing to form a stable cross-linked structure. At the same time, it is difficult to further evenly disperse the three in the system, which affects the stability of the system. Therefore, the performance of Example 13 is reduced.

[0065] The mass of the carbon nanotube composite added in Example 14 and Example 15 is adjusted. When the amount of the carbon nanotube composite added is too little, it is difficult to further fully improve the overall strength of the system, resulting in a decrease in the overall performance of the system. When the content of carbon nanotubes is too much, the system agglomerates, thereby affecting the overall stability and comprehensive performance.

[0066] The carbon nanotube composite in Comparative Example 1 is only modified carbon nanotubes, and a single component is difficult to further improve the overall strength of the system. At the same time, without graphene oxide, the overall antibacterial performance of the system is also difficult to be further improved, so the performance of Example 1 is reduced.

[0067] In Comparative Example 2, the carbon nanotube composite is replaced with modified graphene oxide. A single component is difficult to synergistically improve the mechanical properties of the system, so the performance of Comparative Example 2 is reduced.

[0068] In Comparative Example 3, no carbon nanotube composite was added. The mechanical properties of the gloves without the carbon nanotube composite were difficult to improve, and it was difficult to play an antibacterial role, so the performance of Comparative Example 3 was greatly reduced.

[0069] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A production process for environmentally friendly gloves, characterized by: The steps include: S1. Add a crosslinking agent to the nitrile latex under stirring and continue stirring, then seal and let stand, add a 10% potassium hydroxide aqueous solution and a foam stabilizer by mass and stir after standing, add a sulfur dispersion, a accelerator dispersion and a zinc oxide dispersion to the system and stir, when the viscosity of the latex system increases significantly, increase the stirring speed so that the surface of the system remains in a flowing state, continue stirring, and when the viscosity of the system decreases, add water to reduce the viscosity of the system; S2, adding the carbon nanotube composite material to the system and maintaining the stirring state, when the viscosity of the system increases, increasing the stirring speed, and then adding water to reduce the viscosity of the system; S3, adding thickener and increasing stirring speed, then adding crosslinking agent and keeping stirring, when the viscosity of the system increases, increasing stirring speed, adding latex stabilizer and continuing stirring to make the latex system react completely; S4, stop stirring, seal and let stand, filter and stir after standing, add water to reduce the viscosity of the system, and then stir and foam; S5, putting the glove liner into a mold, then dipping in glue, and then drying, vulcanizing and aging after dipping in glue to obtain environmentally friendly gloves.

2. The production process of an environmentally friendly glove according to claim 1, characterized in that: The step S5 specifically includes the following steps: Put the glove liner on the hand mold, preheat the glove liner, then dip it in glue, take the glue out of the dipped gloves, remove the excess glue, heat and dry, soak in water to clean, and finally dry, vulcanize and mature to obtain environmentally friendly gloves.

3. The production process of the environmentally friendly gloves according to claim 1, characterized in that: The carbon nanotube composite material comprises modified carboxyl carbon nanotubes, modified graphene and ferrosoferric oxide.

4. The production process of the environmentally friendly gloves according to claim 3, characterized in that: The modified graphene oxide includes 2-methylimidazole and graphene oxide.

5. The production process of the environmentally friendly gloves according to claim 4, characterized in that: The modified graphene oxide is prepared by the following method: 2-methylimidazole and methanol are mixed to obtain a 2-methylimidazole solution, zinc nitrate hexahydrate and methanol are mixed to obtain a zinc nitrate solution, graphene oxide, water and methanol are mixed, ultrasonicated, and then mixed with the zinc nitrate hexahydrate solution, stirred, 2-methylimidazole solution is added, ultrasonically stirred to obtain a seed solution, and the seed solution is dried to obtain seeds; after mixing the prepared seeds with methanol, 2-methylimidazole and cobalt nitrate hexahydrate are added, ultrasonically stirred, centrifuged for washing, and dried to obtain modified graphene oxide.

6. The production process of the environmentally friendly gloves according to claim 4, characterized in that: The mass ratio between the graphene oxide and 2-methylimidazole is 1:(2.2-2.4).

7. The production process of the environmentally friendly gloves according to claim 1, characterized in that: The carbon nanotube composite material is prepared by the following method: The modified graphene oxide is mixed with water and then ultrasonically treated to obtain a modified graphene oxide dispersion; modified carboxyl carbon nanotubes, ferric chloride and ferrous sulfate heptahydrate are added to the modified graphene oxide dispersion, and the mixture is stirred in a water bath for reaction; ammonia water is added while stirring; after the reaction is completed, a reducing agent is added for reduction to obtain a composite dispersion; the composite dispersion is dried to obtain a precipitate; the precipitate is naturally cooled and then washed to neutrality; the precipitate is centrifuged and then freeze-dried to obtain a carbon nanotube composite material.

8. The production process of the environmentally friendly gloves according to claim 7, characterized in that: The mass ratio of the modified graphene oxide, the modified carboxyl carbon nanotubes, ferric chloride and ferrous sulfate heptahydrate is (3.8-4.2):1:12:

5.

9. The production process of the environmentally friendly gloves according to claim 7, characterized in that: The reducing agent includes ammonium sulfide.

10. The production process of the environmentally friendly gloves according to claim 3, characterized in that: The modified carboxyl carbon nanotubes are prepared by the following method: The polyethyleneimine is mixed with water to obtain a polyethyleneimine aqueous solution, the carboxylated multi-walled carbon nanotubes are added to the polyethyleneimine aqueous solution, condensed and refluxed in an oil bath, vacuum filtered and washed, and freeze-dried to obtain modified carboxyl carbon nanotubes.

Citation Information

Cited By

  • Environment-friendly butyronitrile glove and preparation method thereof

    CN121319483A

  • Flushing glove and preparation method thereof

    CN121714090A